Transient anomalous diffusion of telomeres in the nucleus of mammalian cells - Bronstein, I; Israel, Y; Kepten, E; Mai, S; Shav-Tal, Y; Barkai, E; Garini, Y (Physical review letters, 2009)
We measured individual trajectories of fluorescently labeled telomeres in the nucleus of eukaryotic cells in the time range of 10(-2)-10(4)sec by combining a few acquisition methods. At short times the motion is subdiffusive with r2 approximately talpha and it changes to normal diffusion at longer times. The short times diffusion may be explained by the reptation model and the transient diffusion is consistent with a model of telomeres that are subject to a local binding mechanism with a wide but finite distribution of waiting times. These findings have important biological implications with respect to the genome organization in the nucleus.